2009
DOI: 10.5551/jat.e565
|View full text |Cite
|
Sign up to set email alerts
|

Low Incidence of Cardiac Events in Statin-Administered Patients in CAG Study

Abstract: Aim:The effect of statins in preventing cardiac events in Japanese coronary artery disease (CAD) patients was studied in a retrospective investigation of 148 patients diagnosed with CAD by coronary angiography (CAG). Methods: Sixty-five patients received statins within 2 weeks after CAG, and 83 patients did not receive statins after CAG. Results: In the statin group, total cholesterol (TC) and low-density lipoprotein cholesterol (LDL-C) were reduced significantly with statin administration (p 0.01). In the non… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2010
2010
2014
2014

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 18 publications
0
4
0
1
Order By: Relevance
“…[18][19][20][21] Of these studies, the landmark MEGA Study clearly revealed that pravastatin significantly reduces cardiovascular disease by 30%, with an 18% decrease in LDL-C in patients without a history of cardiovascular disease, 18) and various fi ndings of the MEGA Study have been cited in the current JAS guideline. 15) However, exactly how pravastatin works in high-risk patients in primary prevention categorized by the JAS guideline has not been well investigated to date.…”
Section: )mentioning
confidence: 99%
“…[18][19][20][21] Of these studies, the landmark MEGA Study clearly revealed that pravastatin significantly reduces cardiovascular disease by 30%, with an 18% decrease in LDL-C in patients without a history of cardiovascular disease, 18) and various fi ndings of the MEGA Study have been cited in the current JAS guideline. 15) However, exactly how pravastatin works in high-risk patients in primary prevention categorized by the JAS guideline has not been well investigated to date.…”
Section: )mentioning
confidence: 99%
“…The cholesterol lowering action of statins (HMG-coenzyme A reductase inhibitors) and its associated reduction in cardiovascular events have been well documented in numerous clinical trials [1][2][3][4] . Traditionally, this beneficial effect of statins has been explained by lowering of plasma cholesterol and sub-sequent reduced progression of atherosclerosis.…”
Section: Introductionmentioning
confidence: 99%
“…It is clear that elevated levels of LDL cholesterol are a major predictor of cardiovascular disease (CVD). In addition, a number of large randomized controlled trials have demonstrated that LDL cholesterol lowering with 3-hydroxy-3-methylglutaryl coenzyme A reductase inhibitor (statin) therapy can substantially reduce CVD-related morbidity and mortality [2][3][4][5] . Thus, recent treatment guidelines, such as the National Cholesterol Education Program Adult Treatment Panel (NCEP-ATP ), have been proposed for LDL cholesterol levels based on the number of risk factors 6) ; however, the guidelines do not take into consideation that seasonal variation in serum LDL cholesterol levels may affect clinical management.…”
Section: Introductionmentioning
confidence: 99%